PENGEMBANGAN MODUL PEMBELAJARAN DENGAN METODE APPLIED BEHAVIOUR ANALYSIS PADA ANAK AUTIS DI TKLB-C DHARMA ASIH PONTIANAK - Riana, Ida; Astuti, Indri; Fadillah, Fadillah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2017)
AbstractThe development of the learning module is based on the lack of graduates of Special Education and the limited teaching materials available in schools. The purpose of developing a learning module to produce a learning media that can be used independently by the teacher. Through learning activities using learning modules is expected to help teachers in applying ABA (Applied Behavior Analysis) method in children with autism. The development procedure refers to the development of Borg and Gall using five stages of data collection, planning, product draft development, expert validation, small group testing, product revision and final product refinement. Data collection technique is done by observation and documentation. Data collection tool is an observation sheet of the implementation of module use and positive response of autistic children toward module learning. Data analysis using qualitative and quantitative.The result of research indicates that the design of module development in this research consists of (1) research phase and data collection (analysis of availability of learning resources, teacher ability analysis, teacher graduate analysis), (2) planning stage to formulate the objectives to be achieved, (3) development (includes competence, indicators, material development), 4 (expert validation stage (media and materials), (5) testing phase (small group), and (6) final product improvement Learning steps using learning modules indicate an increase , this is seen from the observation of the implementation of learning that the average value of 88.8 with high snagat criteria. The positive response of autistic children to the learning module also increased 80 with very high criteria. Key Words: Module, Applied Behavior Analysis Method, Autism